KUTUBXONALARDA INTELEKTUAL O'YINLAR ORQALI KITOBXONLARNI JALB QILISH - Mamataliyeva Shoxista Abduqahhor qizi, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This scientific article analyzes the issues of involving readers in the process of acquiring knowledge through the use of intellectual games in libraries. The results of the article show that the use of intellectual games is an important factor in supporting the cognitive development of readers, developing analytical thinking, and ensuring interdisciplinary integration. The game-based learning model serves as an effective tool for increasing cooperation between readers, forming social skills, and strengthening their motivation for learning. This article discusses the impact of intellectual games on the educational process, the advantages of types of games adapted for the library environment, and their role in the educational process. In addition, the article analyzes methodological approaches aimed at increasing the effectiveness of education through intellectual games.